Teachers’ Instructional Planning and Design for Learners in Difficult Circumstances - Vera, Jayson L. De; Manalo, Mercy O.; Ermeno, Razelle D.; Reyes, Carolyn B. Delos; Elores, Yomiko Danise P. (Jurnal Pendidikan Progresif, 2022)
Teachers' Instructional Planning and Design for Learners in Difficult Circumstances. Objectives: This study examined teachers' practices, planning, and creating of educational materials for all students facing challenges. Methods: The study used phenomenology research to evaluate teachers' planning and design processes. In this study, eight teachers were interviewed in depth. The researchers used coding and theme analysis to interpret textual patterns. Findings: Making instructional resources that are appropriate for your teaching style and your students' skills and situations requires a lot of thought and planning. The teachers' thoughts were as follows: Content and distribution, resources and context, technological integration, adaptability and flexibility. Conclusions: New teaching methods that are more sensitive and flexible to student needs are greatly beneficial. To suit students' educational needs, the study revealed various unique teaching and learning strategies. Keywords: Difficult circumstances, instructional planning, phenomenology.DOI: http://dx.doi.org/10.23960/jpp.v12.i1.202202